Types of Organizational Culture in Private Jordanian Hospitals - Saif, Naser Ibrahim (International Review of Management and Marketing, 2017)
Organizational culture (OC) is vital to an entity’s survival and success. This study explores preferred and dominant kinds of OC based on four types – (1) clans, (2) adhocracies, (3) markets, and (4) hierarchies – in private Jordanian hospitals that implemented quality standards in 2016. The author employed a questionnaire using the Organizational Culture Assessment Instrument and distributed it to 442 employees of accredited hospitals, with an overall response rate of 79%. The author concluded that OC in private Jordanian hospitals comprises a mix of the four types mentioned above. Furthermore, the author found that hierarchy culture is the most dominant, while clan culture prevails the least. In terms of the types of OC that employees prefer, they most frequently choose adhocracies, followed by clans, then hierarchies, then markets. Finally, the findings demonstrate that hospitals need to have facilitators, entrepreneurs, team builders, innovation, and a less demanding workplace. Keywords: organizational culture; private hospitals; Jordan JEL Classification: M14